Graeco-Roman and Egyptian glass : a guide to the exhibition at the National Museum in Prague - Čadík, Jindřich; Národní muzeum v Praze (Prague : National Museum, 1970)
Résumé
Katalog izložbe
Bibliografija: str. 23-25
Keywords: grčko staklo; rimsko staklo; egipatsko staklo